GURU DAN STRATEGI INKUIRI DALAM PEMBELAJARAN BIOLOGI - Indayana Febriani Tanjung (JURNAL TARBIYAH, 2016)
Learning more than just the memorization process and accumulate knowledge , but how knowledge gained meaningful to learners through thinking skills. Biology as one field natural sciences loading process skills include the skills to observe , hypothesize , using tools and materials, ask questions, categorize and interpret the data , and communicate the findings orally or in writing , dig and sort out factual information relevant to test ideas or solve everyday problems. With the strategy of inquiry learners can find the answer to the problems with finding and find your own answers to the proposed teacher .